St. Anne in Renaissance music devotion and politics - Anderson, Michael Alan 1975- (Cambridge University Press, 2014)
Devotion to Saint Anne, the apocryphal mother of the Virgin Mary, reached its height in the fifteenth and early sixteenth centuries. Until now, Anne's reception history and political symbolism during this period have been primarily discussed through the lens of art history. This is the first study to explore the music that honoured the saint and its connections to some of the most prominent court cultures of western Europe. Michael Alan Anderson examines plainchant and polyphonic music for Saint Anne, in sources both familiar and previously unstudied, to illuminate not only Anne's wide-ranging intercessional capabilities but also the political force of the music devoted to her. Whether viewed as a fertility aide, wise mother, or dynastic protector, she modelled a number of valuable roles that rulers reflected in the music of their devotional programmes to project their noble lineage and prestige